Levantamento de Orchidaceae em quatro fragmentos de Campos de Altitude em Campos do Jordão, SP, Brasil - Gonçalves, Gabriel Franco; Sampaio, Daniela; Barros, Fábio De (Instituto de Botânica, 2015)
ABSTRACT Orchidaceae is one of the largest families of Angiosperms, also being one of the richest and with high degree of endemism in the Atlantic Forest, a biome that includes Mixed Rain Forest and Highland Fields, typical of Campos do Jordão. This study aimed to survey the Orchidaceae species present in four highland fields in an Area of Environmental Protection belonging to the Instituto Presbiteriano Mackenzie in Campos do Jordão, São Paulo State, in the district of Umuarama. Monthly expeditions were made from February 16, 2013 to February 15, 2014. In this period, 12 species belonging to nine genera of Orchidaceae were collected. The most representative genera were Coppensia (three species) and Habenaria (two species), being the remaining genera represented by only one species. Several factors that endanger the integrity of these environments were observed, despite these environments being so little valued and not studied enough.

Orchidaceae é uma das maiores famílias das Angiospermas, sendo também uma das mais ricas e com mais alto grau de endemismo na Mata Atlântica, bioma que inclui a Floresta Ombrófila Mista e os Campos de Altitude, típicos da região de Campos do Jordão. Este trabalho teve como objetivo fazer um levantamento das espécies de Orchidaceae ocorrentes em quatro campos de altitude em uma Área de Proteção Ambiental pertencente ao Instituto Presbiteriano Mackenzie em Campos do Jordão, Estado de São Paulo, no bairro de Umuarama. Foram realizadas expedições mensais de 16 de fevereiro de 2013 até 15 de fevereiro de 2014. Foram coletadas, ao todo, 12 espécies pertencentes a nove gêneros, sendo que desses, os mais representativos foram Coppensia (três espécies) e Habenaria (duas espécies), os demais representados por apenas uma espécie. Foram observados muitos fatores que colocam em risco a integridade desses ambientes já tão pouco valorizados e estudados.
Taxonomic survey of the Orchidaceae in four highland fields fragments in Campos do Jordão, São Paulo State, Brazil
Keywords: Area of Enviromental Protection; Atlantic Forest; Taxonomy; Área de Proteção Ambiental; Mata Atlântica; Taxonomia